Influência da aplicação de fertilizantes e fungicida sobre o enchimento de grãos e o desempenho agronômico do arroz irrigado - Camargo, Edinalvo Rabaioli (2007)
Increasing green leaf duration during grain filling in rice, using management practices to enhance plant nutrition and health, can increase grain yield. To test this hypothesis, two experiments were conducted in 2005/06. The first experiment with the objectives of evaluating the effects of nitrogen (N) and fungicide application at booting stage on 1) the green leaf area duration and grain yield and 2) on the evolution of the dry mass accumulation in grains. The treatments were three N rates (50, 100 and 150 kg ha-1) and management practices during the booting stage (supplementary application of 30 kg ha-1 N, fungicide application, and the combination of the previous treatments, including a check treatment). The treatments were arranged in a randomized block design, in a factorial scheme with four replications. Interaction among the treatments was not verified during rice grain filling. Leaf area and senescence, yield, yield components, and evolution and rate of dry mass accumulation in panicle were not affected by the management practices applied on the booting stage. The second experiment had the objective of evaluate the effect of fertilizers applied to seeds or at the booting stage on green leaf maintenance and rice performance. The treatments, which were arranged in a randomized block design with four replications, used ten foliar fertilizers available in the market, two seed treatment products, one fungicide, and a check treatment. The treatments did not affect the variables studied. The average yield was about 10,000 kg ha-1, showing that there was no limitation on plant growth and yield. The products used in this study did not increase the duration of leaf area, the yield and, the grain quality of irrigated rice.